Peer-reviewed Public Health Journals - Nora Mohammed Al-Aboud; Khalid Al Aboud; Ahmad Al Qurashi (Intelektual Pustaka Media Utama, 2015)
Peer-reviewed Public Health journals are essential media for the workers in the public health field. There are already many periodicals published in the public health domain and still many new ones are being added. Journalism in public health is facing many changes and challenges. Technologies and smart phones applications in particular affected the pattern of publication and readership of these journals. This report shed some light on the current peer-reviewed periodicals in the public health.